2014
DOI: 10.4319/lo.2014.59.1.0223
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of UV‐enhanced community respiration for plankton metabolic balance

Abstract: The net community production (NCP) of plankton communities affects their role as sources or sinks of atmospheric CO 2 . Most estimates of NCP have been made by enclosing communities in bottles, generally glass borosilicate, that remove ultraviolet (UV)B and part of UVA wavelengths. A series of experiments were conducted to test whether NCP values from communities incubated excluding UVB (+ part of UVA) radiation (i.e., in glass borosilicate) differ from those of communities receiving the full solar radiation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 43 publications
(54 reference statements)
3
34
1
Order By: Relevance
“…In our study, primary production determined in bottle incubations may have been stimulated relative to in situ rates due to the exclusion of UV radiation in the incubation bottles (e.g. Worrest et al 1980;Agustí et al 2014). Although further studies are needed to evaluate the combined impact of UV radiation and the stimulating effect of nutrient enrichment, the increase in Chl a in ponds and enclosures over time in our study clearly demonstrated that despite potential UV radiation biological production was indeed limited by nutrients.…”
Section: The Effect Of Nutrient Addition On Grazers and Higher Trophimentioning
confidence: 52%
See 1 more Smart Citation
“…In our study, primary production determined in bottle incubations may have been stimulated relative to in situ rates due to the exclusion of UV radiation in the incubation bottles (e.g. Worrest et al 1980;Agustí et al 2014). Although further studies are needed to evaluate the combined impact of UV radiation and the stimulating effect of nutrient enrichment, the increase in Chl a in ponds and enclosures over time in our study clearly demonstrated that despite potential UV radiation biological production was indeed limited by nutrients.…”
Section: The Effect Of Nutrient Addition On Grazers and Higher Trophimentioning
confidence: 52%
“…Wängberg et al 2008) and ciliate biomass (Marangoni et al 2006;Summerer et al 2009). If the bacteria and grazers are more strongly inhibited by UV radiation than are primary producers, UV radiation may thus have a stimulating effect on net productivity in the melt ponds (Agustí et al 2014;Garcia-Corral et al 2014). In our study, primary production determined in bottle incubations may have been stimulated relative to in situ rates due to the exclusion of UV radiation in the incubation bottles (e.g.…”
Section: The Effect Of Nutrient Addition On Grazers and Higher Trophimentioning
confidence: 99%
“…For instance, modifications of the light field (Kirk, 1994) are observed as the incubations have been conducted with borosilicate bottles, a material that excludes UVB radiation. Indeed, recent analyses comparing estimates derived using quartz and glass bottles have shown that estimates of net community production are affected by the removal of the ambient UVB radiation when glass or plastic materials that filter out UV-B radiation are used, as has been the case for most analyses (Godoy et al, 2012;Agustí et al, 2014;Regaudie-de-Gioux et al, 2014). Furthermore, it is rare for in vitro incubations to be carried out at the correct corresponding environmental temperature.…”
Section: An Overview Of Methods To Measure Marine Phytoplanktonic Primentioning
confidence: 99%
“…Also, if incubation techniques are employed the light climate in experimental containers needs to reflect that in the field, which can be challenging. For example, it has recently been demonstrated that borosilicate flasks widely used for experimental incubations filter out UV light resulting in overestimation of production (Agustí et al, 2014). Moreover, the use of incubators allowing the passage of UV light may also mistakenly include the UV photo-oxidation (oxygen sink) in their plankton productivity term, which can lead to an underestimation of NCP (Kitidis et al, 2014;Gieskes et al, 2015).…”
Section: Ranking the Trophic State Of Coastal And Shelf Pelagic Ecosymentioning
confidence: 99%